Analysis of Differences between Expected and Perceived Satisfaction Score of Pilgrims: A Case of Chhinnamasta Temple of Nepal - Shrestha, Yogesh Man; Shrestha, Raju (Nepalese Journal of Hospitality and Tourism Management, 2023)
Nepal has many religious places to visit. The country collected about 6.7 percent of GDP in 2019. For sustainability of revenue collection and conservation of religious sites, the pilgrims should meet their expectations and hence, difference in Expectation (EV) and Perceived Score (PV) is one to asses that the study randomly selected 528 pilgrims visiting the study period was approached and noted their perception on 8 attributes that tap various dimension of pilgrims’ sites using structured 24 Likert Scale Questions. Reliability questions related to each attribute were measured by calculating Cronbach Alpha and McDonald’s Omega. There was no serious problem found regarding reliability of attributes. The Wilcoxon-Signed Rank test was used to infer a significant difference between EV and PV. All attributes except ‘condition on Safety and security’ showed significant difference between PV and EV, of which 3 attributes PV score outweigh EV. Gaps on EV and PV necessitate reviewing facilities available at Chhinnamasta Temple to attract more tourists.